INFLUENCE OF ACADEMIC MOBILITY TO STUDENTS’ INTERCULTURAL COMMUNICATIVE COMPETENCE - Kadirsizova, Shynar; Zhorokpayeva, Meiramgul (Pedagogy and Psychology, 2023)
This paper presents the findings of a study on how students' intercultural communication skills are impacted by academic mobility. In the backdrop of the ever-increasing globalization, the development of young people's intercultural competence as engaged members of society is becoming a daily reality interactions between cultures. The research is aimed at investigating psychological bases of intercultural communicative competence through ethnical identity and tolerance. The study investigated that students, who experienced academic mobility had more positive ethnic identities and demonstrated tolerance in comparison with the students of another group. Thus, it is demonstrated how crucial academic mobility is for developing intercultural communication skills.